1994
DOI: 10.1177/002224299405800301
|View full text |Cite
|
Sign up to set email alerts
|

Socially Responsible Organizational Buying: Environmental Concern as a Noneconomic Buying Criterion

Abstract: The greening of corporate America has added a new and different type of criterion to some organizational buying decisions—social responsibility. Scholars have given little attention to such noneconomic buying criteria. On the basis of a study of 35 buying processes in ten organizations and an in-depth examination of 21 of those processes, the author addresses how and why socially responsible buying comes about in organizations. The findings suggest that two factors have been key to the success of socially resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
264
1
23

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(299 citation statements)
references
References 28 publications
11
264
1
23
Order By: Relevance
“…). Firm and facility level antecedents include top and middle management support (Drumwright ; Carter et al. ; Carter and Jennings ), customers (Simpson et al.…”
Section: Literature Review and Research Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…). Firm and facility level antecedents include top and middle management support (Drumwright ; Carter et al. ; Carter and Jennings ), customers (Simpson et al.…”
Section: Literature Review and Research Modelmentioning
confidence: 99%
“…Indeed, numerous earlier studies have also found that when it comes to supply chain‐related environmental projects, a key success factor is the ability of the project advocate or champion to gain buy‐in or commitment of others in the company (Drumwright ; Handfield et al. ; Crane ; Carter and Jennings ; Carter et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, stakeholder theory suggests that firms should take into account the preferences of their multiple stakeholders to formulate their strategies to win the trust and satisfaction of their key stakeholders (Freeman, 1984; Mitchell et al ., 1997). If companies' decisions are based only on economic goals, incorporating environmental concerns into their strategies may be impossible (Drumwright, 1994). Companies need to adopt long‐term sustainable thinking that relies on noneconomic goals as well as highlighting stakeholder and institutional pressures (Prakash, 2002).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…With the development of a low-carbon economy, sustainable supply chain management has become a hot issue in the academic community. Drumwright [11] pointed out that enterprises should have a sense of social responsibility and focus on social benefits while pursuing economic benefits. Within the theme of low-carbon economy, several scholars have been concerned about the problems of green product design, remanufacturing, green procurement system and reverse logistics [12][13][14][15][16].…”
Section: Sustainable Supply Chain Managementmentioning
confidence: 99%